Earth materials : introduction to mineralogy and petrology - Klein, Cornelis (Cambridge University Press, 2013)
"The fundamental concepts of mineralogy and petrology are explained in this highly illustrated, full-color textbook to create a concise overview for students studying Earth materials. The relationship between minerals and rocks and how they relate to the broader Earth, materials and environmental sciences is interwoven throughout. Beautiful photos of specimens and Crystal-Maker's 3-D illustrations allow students to easily visualize minerals, rocks and crystal structures. Review questions at the end of chapters allow students to check their understanding. The importance of Earth materials to human cultural development and the hazards they pose to humans are discussed in later chapters. This ambitious, wide-ranging book is written by two world-renowned textbook authors each with over 40 years of teaching experience, who bring that experience to clearly convey the important topics"--